Good glycemic control at puberty in boys with type 1 diabetes is important for final height. Issue 12 (10th August 2021) - Shpitzer, Hana; Lazar, Liora; Shalitin, Shlomit; Phillip, Moshe; de Vries, Liat
Abstract: Background: Poor glycemic control in children with type 1 diabetes (T1D) may hinder sexual development and the associated growth spurt. This study aims to identify factors that may affect the timing of puberty, total pubertal growth (TPG), and final height (F‐Ht) in boys with T1D. Methods: This was a retrospective longitudinal study of 68 boys diagnosed with T1D during 1996 to 2009, who were prepubertal at diagnosis and had completed puberty at the time of data collection. Data were accessed regarding anthropometric measurements, Tanner stage, and glycosylated hemoglobin (HbA1c) levels from diagnosis to F‐Ht. F‐Ht was compared to parental height and Israeli National Health Survey data. Results: The mean F‐Ht standard deviation score (F‐Ht‐SDS) was lower than the mean Ht‐SDS at diagnosis ( P < .006) but similar to the mean target height SDS ( P = .3) and to values from the national survey ( P = .12). Mean HbA1c levels in the year preceding pubertal onset were associated with the age at onset of puberty ( R = 0.33, P = .009) and inversely with TPG ( R = −0.3, P = .03). Mean HbA1c levels during puberty were inversely associated with TPG ( R = −0.26, P = .035) and F‐Ht ( R = −0.28, P = .02). Boys who presented with diabetic ketoacidosis at diagnosis were shorter than those who did not throughout the follow‐up. Conclusions: We found associations of age of pubertal onset, pubertal growth spurt, and F‐Ht with target height and glycemic control before and during puberty. Targeted interventions to achieve optimal metabolic control during these time periods are needed for normal, timely puberty and for achieving optimal adult height within the genetic target height. Abstract : Highlights Boys with type 1 diabetes diagnosed before puberty achieved a final height that was similar to that of their target height and the general population. The association of good glycemic control with higher total pubertal growth and final height highlights the importance of maintaining tight glycemic control, especially during the stages of maximal growth when boys may be particularly vulnerable. 摘要: 背景: 1型糖尿病(T1D)儿童血糖控制不良可能会阻碍性发育和生长发育。本研究旨在确定可能影响T1D男孩青春期发育时间、总青春期发育(TPG)和最终身高(F‐Ht)的因素。 方法: 这是一项回顾性纵向研究, 研究对象为1996年至2009年间被诊断为T1D的68名男孩, 他们在被诊断时处于青春期前, 在数据收集时青春期结束。获取从诊断到F‐Ht的人体测量、Tanner分期和糖化血红蛋白(HbA1c)水平的数据。将F‐Ht与父母身高和以色列国民健康调查数据进行比较。 结果: 诊断时F‐Ht标准差得分(F‐Ht‐SDS)低于Ht‐SDS平均值(P<0.006), 与靶高度SDS平均值(P=0.3)和全国普查值(P=0.12)相近。青春期开始前一年的平均HbA1c水平与青春期开始年龄呈正相关(R=0.33, P=0.009), 与TPG呈负相关(R= ‐0.3, P=0.03)。青春期平均HbA1c水平与TPG(R=‐0.26, P=0.035)和F‐Ht(R=‐0.28, P=0.02)呈负相关。在诊断时以糖尿病酮症酸中毒为起病的男孩在整个随访过程中的身高要比那些没有酮症酸中毒的男孩要矮。 结论: 我们发现青春期开始年龄、青春期生长增速期和F‐Ht与青春期前和青春期期间的目标身高和血糖控制相关。在这些时间段内实现最佳代谢控制的针对性干预对于在遗传目标身高范围内达到最佳成人身高是必要的。